The Impact of Korean Culture and Its Language Addicted For Indonesian Teenagers of Korean-Lovers - Siti Rahmi (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2020)
This study focused on (a) the impact of Indonesian teenagers addicted of Korean lovers in learning Korean culture and its language; (b) to find out the advantages and disadvantages of Indonesian teenagers addicted of Korean lovers in learning Korean culture and its language. This study used 50 students of MAN 2 Mataram as the members of the K-lovers (Manda Korean Club) and as the research participants.This study is qualitative and the data collected through reading some research papers and depth interview with Korean lovers members/community and one of the native speaker.The data were analyzed by descriptive analysis technique.This study result showed that (a) Korean culture and its language was giving many impacts for the teenagers of Indonesia addicted of Korean lovers; (b) the researcher found many advantages and disadvantages of Indonesian teenagers of Korean lovers in learning Korean culcure and its language. Besides that, the researcher found during research about intercultural communication. Intercultural communication occurs when two or more people with different cultural background.The results of this study are recommended to (a) all Korean lovers in Indonesia which encourage the development and utilization of learning Korean culture and its language, (b) Korean teachers to use this study as an alternative material and developing students motivation based on their needs, (c) others researcher to carry out further investigation with broader scope of content, focus and locus, and more participants to be involved. Keywords: addict, culture, impact, Korean lovers, language.